PqsA mutation-mediated enhancement of phage-mediated combat against Pseudomonas aeruginosa - Su, Qiao; Lu, Di; Kong, Jiuna; Lin, Hong; Xuan, Guanhua; Wang, Jingxue (Frontiers in Cellular and Infection Microbiology, 2024)
Phage therapy is a potential approach in the biocontrol of foodborne pathogens. However, the emergence of phage resistance and the narrow host range of most phage isolates continue to limit the antimicrobial efficacy of phages. Here, we investigated the potential of the pqsA gene, encoding the anthranilate-CoA ligase enzyme, as an adjuvant for phage therapy. The knockout of the pqsA gene significantly enhanced the bactericidal effect of phages vB_Pae_QDWS and vB_Pae_S1 against Pseudomonas aeruginosa. Under phage infection pressure, the growth of the PaΔpqsA was significantly inhibited within 8 h compared to the wild-type PAO1. Furthermore, we found that altering phage adsorption is not how PaΔpqsA responds to phage infection. Although pqsA represents a promising target for enhancing phage killing, it may not be applicable to all phages, such as types vB_Pae_W3 and vB_Pae_TR. Our findings provide new material reserves for the future design of novel phage-based therapeutic strategies.